2019
DOI: 10.1111/jcmm.14745
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between cancer‐associated fibroblasts and immune cells in cancer

Abstract: Multiple studies have shown that cancer‐associated fibroblasts (CAFs) play an important role in tumour progression, including carcinogenesis, invasion, metastasis and the chemoresistance of cancer cells. Immune cells, including macrophages, natural killer cells, dendritic cells and T cells, play a dual role in the tumour microenvironment. Although increasing research has focused on studying interactions between distinct cells in the tumour microenvironment, the complex relationships between CAFs and immune cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 120 publications
(276 reference statements)
3
69
0
Order By: Relevance
“…In our study, we also isolated two subtypes of CAFs, apCAFs and the traditional myCAFs. Previous studies suggested that apCAFs could activate CD4+ T cells and act as the immune-modulator [50]. We found the ratio of apCAF/myCAF in primary tumor tissue was dramatically higher than that in pulmonary metastatic and recurrent tumor tissues, suggestive of the difference of the TME of OS in the primary versus the metastatic tumor.…”
Section: Discussionmentioning
confidence: 59%
“…In our study, we also isolated two subtypes of CAFs, apCAFs and the traditional myCAFs. Previous studies suggested that apCAFs could activate CD4+ T cells and act as the immune-modulator [50]. We found the ratio of apCAF/myCAF in primary tumor tissue was dramatically higher than that in pulmonary metastatic and recurrent tumor tissues, suggestive of the difference of the TME of OS in the primary versus the metastatic tumor.…”
Section: Discussionmentioning
confidence: 59%
“…For example, activated CAFs account for up to 90% of total PDAC tumor volume [ 6 , 9 , 41 ]. Activated CAFs are known to support tumor growth and secrete chemokines and cytokines like TGFβ, vascular endothelial growth factor-A (VEGF-A), other angiogenic factors, prostaglandin-2 (PGE2), and indolamine-2,3-dioxygenase (IDO) to promote immunosuppression, where the latter is known to be secreted by inflammatory CAFs [ 6 , 9 , 40 , 42 , 43 ]. Increased TGFβ and VEGF-A secretion by CAFs also increases regulatory T-cell (T-reg) infiltration in adenocarcinomas [ 43 ].…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
“…Activated CAFs are known to support tumor growth and secrete chemokines and cytokines like TGFβ, vascular endothelial growth factor-A (VEGF-A), other angiogenic factors, prostaglandin-2 (PGE2), and indolamine-2,3-dioxygenase (IDO) to promote immunosuppression, where the latter is known to be secreted by inflammatory CAFs [ 6 , 9 , 40 , 42 , 43 ]. Increased TGFβ and VEGF-A secretion by CAFs also increases regulatory T-cell (T-reg) infiltration in adenocarcinomas [ 43 ]. TGFβ, PGE2, and IDO are also known to downregulate NCRs and inhibit cytokine secretion from NK cells [ 44 ], thus decreasing their cytotoxicity.…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
“…Growing evidence has shown that the TME is one of the key determinants of the tumor immune response, and CAFs are closely associated with the efficacy of immunotherapy [161]. CAFs directly interact with immune cells by secreting growth factors, cytokines and chemokines, thus mediating and regulating the infiltration of immune cells [162]. In addition, CAFs can also create a physical immune barrier through ECM remodeling to exert immunomodulatory effects [163].…”
Section: Mirnas In Cafs and Cancer Immunosuppressionmentioning
confidence: 99%